Prevalence of sexually transmitted infections and associated factors in the inmate population of the Chachapoyas correctional center, Peru - Victor Juan Vera-Ponce; Luis M. Rojas; Christian J. Campos; Roxana Cubas; Jhony A De LaCruz-Vargas; Stella M. Chenet; Rafael Tapia-Limonchi (Archives of Public Health)
Abstract Background The objective of the study was to assess the prevalence of sexually transmitted infections (STIs) such as HIV, syphilis, viral hepatitis, and human T-lymphotropic virus types I and II (HTLV I-II) among inmates at the Chachapoyas Correctional Center. The risk factors associated with increased transmission of these infections were also determined. Methods This study was observational, analytical, and cross-sectional. It used a non-probabilistic convenience sampling method to select inmates who consented to participate and could provide a blood sample. Samples were collected between November and December 2022. Serological tests were performed to diagnose HIV, syphilis, hepatitis B, hepatitis C, and HTLV I-II. Additionally, demographic and behavioral data were collected through surveys. Results The prevalence of STIs in the sample was 21.31%. Significant associated factors included older age, extended duration of incarceration, and risk behaviors such as sharing personal items. There was a noted low prevalence of previous STI history and low levels of education among the studied population. Conclusions The study emphasizes the significant prevalence of STIs among inmates at the Chachapoyas Correctional Center. It underscores the necessity of implementing specific sexual health programs and STI prevention measures in this environment. The findings highlight the importance of enhancing health services and sexual health education in prisons to minimize STI transmission and promote better conditions for public health equity.